A network approach to investigating the inter-relationship between health-related quality of life dimensions and depression in 1735 Chinese patients with heterogeneous cancers - Muhetaer, Sulaiman; Mijiti, Peierdun; Aierken, Kaibinuer; Ziyin, Huang; Talapuhan, Wulan; Tuoheti, Kaibinuer; Lixia, Ye; Shuang, Qi; Jingjing, Wei (Frontiers in Public Health, 2024)
We aimed to explore the inter-connection between depression and HRQOL dimensions in cancer patients using network approach, which might provide new insights for precise interventions to improve cancer patient's overall HRQOL.Between June 1, 2016 and August 31, 2017, a total of 1735 eligible patients with heterogeneous types of cancer were recruited. The Zung Self-Rating Depression Scale (SDS) andThe European Organization for Research and Treatment of Cancer Quality of Life Questionnaire (EORTC QLQ-C30) were used to measure patients' depression status and HRQOL, respectively. A regularized partial correlation network was established. Central and bridge symptoms/functions were identified using expected influence and bridge expected influence. A directed acyclic graph (DAG) was used to explore the possible causal relationship between depression and HRQOL dimensions.Results: In this study, depression and 15 dimensions of EORTC-QLQ-C30 scale were highly inter-correlated and could be represented as a network. We found that nearly two thirds of cancer patients experienced various degrees of depression, and depression was consistently the central symptom in the network, in addition to nausea/vomiting, pain and physical function. DAG and bridge symptom indicated depression might influence overall HRQOL in cancer patients mainly through emotional function, pain, physical function and sleeplessness, particularly in cancer patients with moderate-to-severe depression. Disparity in network structures between mild and moderate-to-severe depression suggested that the relationship between depression and HRQOL dimensions might be bidirectional.Prevalence of depression remained high in Chinese patients with cancer, and depression may influence various symptoms and functions within HRQOL network. Screening and early treatment of depression was warranted to improve overall HRQOL of cancer patients, in addition to adequate treatment of pain and nausea/vomiting and improvement in physical function.